Effect of Some Heavy Metals on Testosterone Hormone in Infertile Men (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background:  Infertility is defined as a failure of achieve a pregnancy after one year and more of regular unprotected sexual intercourse. The exposure of reproductive system to heavy metals has also been associated with male infertility. A large number of metals are toxicants to the reproductive system and are suspected to be endocrine system disruptors.  Patients and methods:  This study performed at the high institute of infertility diagnosis and assisted reproductive technologies in Al-Nahrain University and the Poisoning consultation center / specialized surgeries hospital in the Medical city in period from November 2018 to April 2019.  Number of 150 men were enrolled in this study divided into two groups, the patient and the normal control groups. The infertile group included 100 men aged 20-50 years who they have abnormal seminal fluid analysis parameters. The second group included 50 healthy fertile men who have at least two children without any previous history of systemic diseases as a control group. Heavy metals and testosterone concentrations were estimated for all the study groups. Aim of current study are evaluation of some heavy metals concentrations, in serum and whole blood of groups. Assessment of testosterone hormone in serum of infertile men and healthy controls and study the correlation between this hormone and trace elements which were estimated among cases.Results: The heavy metals Cu, Pb and Cd showed a highly significant increase (p